Pengaruh Motivasi Belajar, Aktivitas Belajar, dan Teman Sebaya terhadap Kemampuan Matematis Mahasiswa dalam Mata Kuliah Teori Ekonomi Mikro - Nurhasanah, Adinda Mutiara; Hermawan, Yoni; Aisyah, Iis (Civiliza Publishing, Indonesia., 2023)
This research problem originates from learning difficulties focused on students' mathematical abilities, especially in microeconomic theory courses. With various backgrounds, the differences in the abilities of each student, including those originating from learning motivation, learning activities, and peers. This research method uses a survey. The population in this study were students of Economics Education at the Teaching and Education Faculty of Siliwangi University Class of 2019, 2020, and 2021, totaling 323 students with a sample of 179 students. The data collection techniques in this study also used questionnaires and documentation. As data analysis techniques used were prerequisite analysis tests with normality tests, linearity tests, multicollinearity tests, and heteroscedasticity tests, then using statistical analysis multiple linear regression tests and hypothesis testing with the F test (Simultaneous), t-test (partial) and the coefficient of determination. The research results show that the coefficient of determination (R square) in this study is 0.643 or 64.3%. The study results show that: 1) Learning motivation positively and significantly affects students' mathematical abilities in the microeconomic theory course with a sig. 0.031 and t-count 2.172 and a large influence of 23.9%. 2) Learning activities positively and significantly affect students' mathematical abilities in microeconomics theory courses with sig. 0.027, and t-value count of 2.235, and a large influence of 21.2%. 3) Peers positively and significantly affect students' mathematical abilities in microeconomics theory courses with sig. 0.033 and t-value count 2.146 and a large influence of 19.2%. 4) a positive and significant influence exists between learning motivation, learning activities, and peers on students' mathematical abilities in the microeconomic theory course with a sig. 0.033 <0.05 and Fcount value 6.848 > Ftable 2.656.